Self-Reports of Illegal Activity, SCL-90–R Personality Scales, and Urine Tests in Methadone Patients. Issue 3 (December 2015) - Cernovsky, Zack; Sadek, Gamal; Chiu, Simon
In routine work, medical staff usually has to rely on the patient's self-reports of criminal activity and of recent involvement in fights. This study examines how these self-reports of crime correlate with the patients' routine urine tests and personality measures. Pearson correlations of these self-reports by 55 methadone patients ( M age = 34.1 yr., SD = 9.1; 35 men, 20 women) were calculated to their urine screening tests (those for opiates, benzodiazepines, and cocaine) and to personality scores on the Symptom Checklist 90-Revised (SCL-90-R). Patients who reported being involved in recent illegal activities to obtain drugs had significantly higher scores on the SCL-90-R scale assessing obsessive-compulsive symptoms ( r = .28) and had more frequent positive urine tests for cocaine ( r = .35). Those who reported having engaged in fights within the last 12 mo. had higher scores on SCL-90-R measures of somatic complaints ( r = .32), anxiety ( r = .31), and depression ( r = .29), and of overall psychopathology ( r = .29), and they also had more often positive urine tests for cocaine ( r = .28) than other patients. Studies on larger samples are needed to help clinicians to predict criminal or hostile behavior during methadone treatment.